PERT AND THE AUDITOR. - Burgber, Peter H. (The Accounting Review, 1964)
In July, 1962, all companies working on research and development contracts for the U.S. Department of Defense or the U.S. National Aeronautics and Space Administration were advised by those agencies that they would be expected, in the future to employ (PERT) in planning and controlling their contract work. Program Evaluation and Review Technique (PERT) and Critical Path Method (CPM) are in wide use in the chemical and construction industries today and successful applications have been reported in many other fields as well. In essence, PERT permits the combination of the systems concept and the computer into a control technique which shows the way to the optimum allocation of resources. The use of PERT permits the development of more realistic and more detailed time and cost estimates against which actual progress can be measured. Perhaps the principal benefit denying from the routine application of PERT is more accurate projection of resource requirements through the systematization of planning. There has been a growth in the application of PERT technique in the industrial nations.